The Effect of Climate Conditions on COVID-19: A Modelling Study in The Indonesian Epicenter - Yoerdy Agusmal Saputra; Disa Hijratul Muharramah; Ayu Novitrie; Ladyka Viola Armawan; Maurend Yayank Lewinsca; Putri Utami (Jurnal Ners, 2025)
Over 200 countries have experienced a further increase in COVID-19 cases and this has been considered to be influenced by climatic conditions. The most vulnerable countries to this increase are those with low vaccination rates. This study aims to determine the influence of climate on COVID-19 cases in Indonesia. Furthermore, an ecological study design based on time conducted in Jakarta was used to obtain secondary data from March to September 2020. These data include maximum, minimum and average temperature, humidity, precipitation, maximum, and average wind speed, and solar radiation. The multiple linear regression test results showed that high humidity significantly affects the decrease in COVID-19 cases and 66.5% of the variations can be explained by this factor. For every 1% increase in humidity, there will be a decrease of 4 cases per week. However, the high humidity environment was reported to have the ability to suppress cases since transmission is still possible. Therefore, SARS-CoV-2 can still survive in humid conditions but in a relatively short time. Kata Kunci: Climate, COVID-19, epicenter, humidity.